KREATIVITAS GURU PAI DALAM MENCIPTAKAN SITUASI PEMBELAJARAN EFEKTIF PADA KELAS X DI SMKN 1 TANJUNG RAYA - Resvi Anisa; Wedra Aprison; Iswantir M; Arman Husni (Universitas Pahlawan Tuanku Tambusai, 2022)
Based on the observations made by the author, it appears that there are several things that cause the learning situation to be less effective, namely students who are sleepy when learning takes place, are noisy, and often go in and out of class. The purpose of this study was to determine the forms of creativity of PAI teachers in creating effective learning situations in class X at SMKN 1 Tanjung Raya. This study uses a qualitative descriptive approach using key informants, namely Islamic religious education teachers, and supporting informants for class X students. In collecting data, the authors use observation and interview methods. The data analysis technique that the author uses is data reduction, data display, conclusions and data verification, and to test the validity of the data the author uses data triangulation. Based on research conducted by the author regarding